2015
DOI: 10.1136/bmjspcare-2014-000838.3
|View full text |Cite
|
Sign up to set email alerts
|

Research Priority Setting in Palliative and End of Life Care: The James Lind Alliance Approach Consulting Patients, Carers and Clinicians

Abstract: IntroductionThere can be a mismatch between what the public see as important unanswered questions and those which are actually researched. The Palliative and end of life care Priority Setting Partnership, facilitated by the James Lind Alliance (JLA), identified and prioritised questions about palliative and end of life care that people in the last years of life, current/bereaved carers and professionals feel are important for research to address.Aim(s) and method(s)A UK public survey (December 2013–April 2014)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…The top four research themes (see Table 2 ) identified in the workshops represent important areas for future research. They broadly overlap with the research priorities identified by the Palliative and end of life care Priority Setting Partnership (PeoPSP) in the UK, which used surveys and NGT to gain consensus from 1043 patients, carers and professionals [ 61 ]. It is to these themes that we now turn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top four research themes (see Table 2 ) identified in the workshops represent important areas for future research. They broadly overlap with the research priorities identified by the Palliative and end of life care Priority Setting Partnership (PeoPSP) in the UK, which used surveys and NGT to gain consensus from 1043 patients, carers and professionals [ 61 ]. It is to these themes that we now turn.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to assess how the proposed research priorities align with the priorities of national agencies and governments across Europe (for example, with national palliative care research agendas, such as the UK Palliative and end of life care Priority Setting Partnership [ 61 ]) as this would give further leverage for obtaining research support. Careful consideration is then needed to determine which of the identified research themes (or sub-themes) need European-wide collaborations, and which specific research questions are best answered within national borders, given the wide variation in service provision and palliative care development [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Priority setting methods have been established and used by almost 30 JLA PSPs, including prostate cancer [19], vitiligo [20], palliative and end of life care [21], childhood neurodisability [22], and dystrophic epidermolysis bullosa [23]. Details of the methods agreed and adopted can be found in a number of publications [24][25][26][27][28], and therefore only a brief summary is presented here.…”
Section: Methodsmentioning
confidence: 99%
“…15 A clear understanding of the sources of unsafe care has emerged as a top research priority for patient groups and policymakers. 16…”
Section: Introductionmentioning
confidence: 99%